Proceedings of the Tenth ACM Symposium on Access Control Models and Technologies 2005
DOI: 10.1145/1063979.1064001
|View full text |Cite
|
Sign up to set email alerts
|

Verifiable composition of access control and application features

Abstract: Access control features are often spread across and tangled with other functionality in a design. This makes modifying and replacing these features in a design difficult. Aspect-oriented modeling (AOM) techniques can be used to support separation of access control concerns from other application design concerns. Using an AOM approach, access control features are described by aspect models and other application features are described by a primary model. Composition of aspect and primary models yields a design m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Kim et al represent RBAC policies as UML patterns that are then instantiated on a model, using UML template diagrams [24]. Song et al use Aspect-Oriented Modelling to represent RBAC policies as crosscutting concerns in a UML model, and provides support for verifying properties that the model should satisfy [38]. Sun et al translate UML models to Alloy in order to verify properties using a SAT solver [39].…”
Section: Access Control and Verificationmentioning
confidence: 99%
“…Kim et al represent RBAC policies as UML patterns that are then instantiated on a model, using UML template diagrams [24]. Song et al use Aspect-Oriented Modelling to represent RBAC policies as crosscutting concerns in a UML model, and provides support for verifying properties that the model should satisfy [38]. Sun et al translate UML models to Alloy in order to verify properties using a SAT solver [39].…”
Section: Access Control and Verificationmentioning
confidence: 99%
“…However, it focuses only on how to model RBAC and MAC systems in UML without considering how this approach can be used to design a secure software system. In another effort [27], Ray et al integrate RBAC and MAC policies into an application using an aspect-oriented approach to separate access control features from other application features.…”
Section: State Of the Art Surveymentioning
confidence: 99%
“…Many contributions have been presented in the state of the art for specifying and enforcing security at UML design [1,2,4,5,6,7,8,14,16,17,18,19,20,22,23,27,28,30]. While sharing almost the same objectives, these contributions Cite this document as follows: http://www.jot.fm/general/JOT template LaTeX.tgz * The research leading to this work was possible due to funding and scientific collaboration with Software Research, Ericsson Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [39] have demonstrated the use of a role-based access control (RBAC) within the AOM approach [4]. However, the approach where XACML can be used as it is to specify the access control policies is more suitable.…”
Section: Aom Approachesmentioning
confidence: 99%